Timescales of Birkeland Currents Driven by the IMF. Issue 14 (24th July 2019) - Coxon, John C.; Shore, Robert M.; Freeman, Mervyn P.; Fear, Robert C.; Browett, Stephen D.; Smith, Andrew W.; Whiter, Daniel K.; Anderson, Brian J.
Abstract: We obtain current densities from the Active Magnetosphere and Planetary Electrodynamics Response Experiment (AMPERE), alongside B y and B z from the Interplanetary Magnetic Field (IMF) for March 2010. For each AMPERE spatial coordinate, we cross‐correlate current density with B y and B z, finding the maximum correlation for lags up to 360 min. The patterns of maximum correlation contain large‐scale structures consistent with the literature. For the correlation with B y, the lags on the dayside are 10 min at high latitudes but up to 240 min at lower latitudes. Lags on the nightside are 90–150 min. For B z, the shortest lags on the dayside are 10–20 min; on the equatorward edge of the current oval, 60–90 min; and on the nightside, predominantly 90–150 min. This novel approach enables us to see statistically the timescales on which information is electrodynamically communicated to the ionosphere after magnetic field lines reconnect on the dayside and nightside. Plain Language Summary: We take the minute‐by‐minute behavior of the interplanetary magnetic field (which is in the solar wind) and electric currents flowing along Earth's magnetic field lines in the Northern Hemisphere. We move them with respect to one another to find the time lag required to make them agree best, and then note the best agreement and the time lag that we found. We plot both of these quantities on maps of the Earth's Northern Hemisphere, and then analyze these maps to uncover new information about Earth's reaction to the solar wind. Key Points: We cross‐correlate Birkeland current density with IMF B y and B z and find morphology of R1/R2 and other current systems B z direct driving timescales are 10‐20 min; expanded polar cap timescales, 60‐90 min; and nightside timescales, 120‐150 min B y shows 10‐min timescales on the dayside at high latitudes, but lags up to 240 min elsewhere